Evaluation of Planning for The Completion of Nine Years of Compulsory Basic Education - Hary Murcahyanto; Mohzana; Hartini Haritani (Nazhruna: Jurnal Pendidikan Islam, 2024)
This study focuses on the evaluation of the planning of 9-year compulsory basic education in East Lombok Regency, with the main objective of assessing the effectiveness of planning oriented to minimum service standards (MSS). This education planning is considered important in addressing the gap in access to education and improving the quality of basic education at the regional level. The research hypothesis is that the proper implementation of MSS in basic education planning can significantly improve access and quality of education and reduce illiteracy rates in the region. This research method combines qualitative and quantitative approaches through in-depth interviews, observations, and documentation, involving stakeholders such as education officials, school principals, and community leaders. This study found that the planning structure and products have included an in-depth analysis and appropriate budget allocation, but budget challenges and community support are aspects that need to be improved. The discussion of the research results emphasizes the importance of involving the community more actively and strengthening cross-sectoral collaboration to optimize the planning and implementation of basic education. Overall, this study makes a significant contribution to understanding the complexity of basic education planning in the region and offers recommendations for increasing the effectiveness of SPM implementation, which can play a role in improving the quality of education and reducing educational disparities in East Lombok Regency.